A double‐blind, randomized, vehicle‐controlled efficacy assessment study of a skin care formulation for improvement of mild to moderately severe acne. (4th June 2013) - Angelova‐Fischer, I.; Rippke, F.; Fischer, T.W.; Neufang, G.; Zillikens, D.
Abstract: Background: Inflammation, increased sebum production and P. acnes colonization are key factors in acne pathogenesis. Cosmetic formulations based on a combination of active compounds with in vitro proven anti‐inflammatory, sebum regulating and P. acnes reducing properties may therefore contribute to improve the clinical signs and associated burden of disease. Objective: To provide in vivo proof‐of‐concept, we performed a 9‐week, double‐blind, randomized, vehicle‐controlled study to assess the stand‐alone efficacy of a skin care formulation containing licochalcone A, l ‐carnitine and 1, 2‐decanediol in volunteers with mild to moderately severe acne (10–25 inflammatory lesions) involving the face. Materials and methods: After enrolment followed by a 1‐week standardization of the cleansing procedure, 60 volunteers aged 14–40 years (40 women and 20 men, mean age 22.4 years) were randomized into two groups of 30 volunteers each, to apply either the active formulation or the vehicle twice daily on the face for 8 weeks. Reduction in the lesion count, P. acnes and sebum levels, stratum corneum hydration, Dermatology Life Quality Index (DLQI) and skin tolerability, assessed after 4 and 8 weeks were defined as outcomes. Results: Compared to baseline, the active formulation group showed at the end of the study a reduction in the mean total lesions count and papular lesions, significant reduction in the pustules ( P  < 0.05) and sebum levels ( P  < 0.01), marked reduction in P. acnes and improvement of DLQI. No significant changes in the respective parameters were found in the vehicle group. At the end of the study, greater reduction in the total lesion count, papules and pustules, P. acnes colonization, sebum production and more pronounced improvement of life quality in the active formulation group compared to the vehicle were found. Conclusions: Our results provide evidence for improved outcomes in result of the application of the active formulation compared to the vehicle from both physician's and patient's perspective.